Prevalence of Sarcopenic Obesity in Adults with Class II/III Obesity Using Different Diagnostic Criteria - Carlene A. Johnson Stoklossa; Arya M. Sharma; Mary Forhan; Mario Siervo; Raj S. Padwal; Carla M. Prado (Journal of Nutrition and Metabolism)
Background/Objective. Sarcopenic obesity (SO) is a hidden condition of reduced lean soft tissue (LST) in context of excess adiposity. SO is most commonly reported in older adults and both its risk and prevalence increase with age. A variety of body composition indices and cut points have been used to define this condition, leading to conflicting prevalence and risk prediction. Here, we investigate variability in the prevalence of SO in an adult sample of individuals with class II/III obesity (BMI ≥ 35 kg/m2) using different diagnostic criteria. Methods. SO definitions were identified from a literature review of studies using dual-energy X-ray absorptiometry (DXA) to assess LST. Demographics, anthropometrics, and body composition (by DXA) were measured in n=120, 86% female (46.9 ± 11.1 years). Results. LST was extremely variable in individuals, even with similar body sizes, and observed across the age spectrum. The prevalence of SO ranged from 0 to 84.5% in females and 0 to 100% in males, depending upon the definition applied, with higher prevalence among definitions accounting for measures of body size or fat mass. Conclusion. SO is present, yet variable, in adults with class II/III obesity. Accounting for body mass or fat mass may identify a higher number of individuals with SO, although risk prediction remains to be studied.